Taxation of new nicotin products - Labiche, Alexandra; Zídková, Hana; Tepperová, Jana; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
This thesis explores the taxation policies of heated tobacco products in the Czech Republic, critically analyzing the implications of the current tax structure on government revenue. As traditional smoking rates decline globally, heated tobacco products have gained popularity, prompting a need to reevaluate existing tax frameworks. This study examines the excise duty rates applied to heated tobacco compared to traditional cigarettes, assessing their effectiveness in enhancing fiscal revenues. The research employs a comparative approach, analyzing data from the Czech market and tax policies in neighboring European countries to provide a comprehensive overview of the tax landscape. Findings suggest that the current lower tax rates on heated tobacco products may contribute to increasing consumption, yet limiting potential tax revenues. The thesis argues for a reformation of tax rates on heated tobacco to align more closely with those of traditional cigarettes, which could lead to increased government revenue.
Vedoucí práce: Hana Zídková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses